PENGARUH PENDEKATAN STEM TERHADAP HASIL BELAJAR IPAS SISWA SEKOLAH DASAR - Halimah, Siti; Encep Supriatna (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
One of the educational innovations that has improved student learning outcomes, particularly in Natural and Social Sciences (IPAS) topics in elementary schools, is the STEM (Science, Technology, Engineering, and Mathematics) approach. The purpose of this essay is to examine how the STEM approach affects the scientific learning results of elementary school pupils. By examining numerous empirical papers released between 2022 and 2024, this study employs a literature review methodology. The study's findings demonstrate that applying the STEM method can improve students' enthusiasm to learn, critical thinking abilities, and conceptual understanding. Additionally, through project-based learning, this method aids pupils in fostering their creativity and teamwork. This article suggests that elementary schools adopt a STEM curriculum widely in order to promote 21st century learning and develop a generation that is prepared to take on problems.